Organizational and managerial challenges of reforming Slovenian public agencies - Kovač, Polonca (Organizacija (Kranj), 2014)
Introduction: Agencies are among the key contemporary public organizations, prospering within reforms carried out worldwide to increase professionalism and rationalism in public administration (PA). Hence, countries have been establishing agencies and delegating them public tasks in order to achieve expertise-based instead of politically-driven and thus more efficient public policies. In such context, the present article addresses the most important strategic documents related to public administration reform (PAR) in Slovenia, analyzing their goals in terms of agencification and the main implementation results and gaps. Research Design: The research is dedicated to exploring the governmental approach to agencification as a key aspect of PAR. It analyzes (1) the main PAR strategic documents on public agencies in Slovenia since the mid-90s, and (2) the perceived implementation of structural and managerial autonomy as the declared goal of agencification. Combined research methods are applied, including descriptive analysis, regional comparisons, structural interviews among representatives of public agencies and their parent ministries, and selected statistical data analysis. Results: As proven by different research methods, the hypothesis whereby agencification goals in Slovenia are largely achieved as part of PAR documents in terms of autonomous organizational structure was confirmed. A more elaborated agencification in PAR documents relates to higher implementation of autonomy. Conclusion: Nevertheless, the professionalism of Slovenian agencies is still an on-going process, particularly as regards the efficiency implementation gap. As for the future, a more consistent PAR incorporating cross-sectoral policy on agencies is required to pursue the development of a democratic and efficient PA.
Keywords: javna uprava; management; reforma; profesionalizacija; agencije; autonomy; avtonomija; organizacija; organization; vodenje; Slovenia; Slovenija